Eurosystem Monetary Targeting: Lessons from U.S. Data - Glenn D. Rudebusch; Lars E. O. Svensson (Sveriges Riksbank, 1999)
Using a small empirical model of inflation, output, and money estimated on U.S. data, we compare the relative performance of monetary targeting and inflation targeting. The results show that monetary targeting would be quite inefficient, with both higher inflation and output variability. This is true even with a deterministic money demand formulation. In this framework, there is thus no support for the prominent role given to money growth in the Eurosystem's monetary policy strategy.
Keywords: E42; E52; E58; 330; Inflation targeting; Monetary targeting; ECB